National R&D systems and technology development in Asia - DE MEYER, Arnoud Cyriel Leo (Institutional Knowledge at Singapore Management University, 2014)
Throughout Asia there has been a significant commitment to investments in research and development, though mainly in the fields of the traditional science and technology (S&T). In the many of the multi-year plans developed by governments in China, East and South East Asia it is considered essential to invest in S&T to grow the economy. These good intentions are not always followed through in practice, but there is undeniably an intention to use S&T as a lever to enhance productivity and create wealth.